Perlindungan Hukum bagi Petani dalam Melaksanakan Jual Beli Hasil Pertanian Melalui Harga yang Ditetapkan oleh Pengepul - Ayu Rosanti, Dyah (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Farmers play a crucial role in food security and the national economy; however, they often face uncertainty in selling their agricultural products, particularly when prices are unilaterally determined by collectors. The imbalance of bargaining power between farmers and collectors frequently results in farmers receiving low prices that do not align with their production costs. This study aims to analyze the legal protection available for farmers in agricultural trade transactions and identify regulatory measures that can ensure fairness in pricing mechanisms. The research adopts a normative juridical approach by examining relevant laws, legal doctrines, and case studies on agricultural trade practices. The findings indicate that although regulations exist to protect farmers, their implementation remains suboptimal. Many farmers lack access to legal information and available protection mechanisms, making them vulnerable to price exploitation by collectors. Therefore, policy strengthening is needed in the form of stricter regulations on price transparency, farmer empowerment through cooperatives or alternative marketing institutions, and more effective law enforcement to safeguard farmers' welfare. With stronger legal protection, farmers are expected to achieve fairer selling prices and contribute to the sustainability of the agricultural sector in Indonesia.